A programme to assist nurses exposed to vicarious traumatisation - Ribeiro, José Francisco (University of the Free State, 2004)
Nurses comprise the largest group of health workers in South Africa. They provide the main connection with patients and have the most direct one-to-one contact with patients. This intensive caring by nurses can result in their experiencing of vicarious traumatisation (VT). This is not only a short-term reaction to working with patients’ traumatic material but also a long-term alteration in the nurses’ own cognitive schemas, beliefs, expectations, and assumptions about the self and others. Consequently nurses are less likely to provide optimal patient care, thus affecting their ability to provide for patients’ well-being. In addition, the consequences of VT also extend to the nurses’ psychological and physical well-being. The objective of this study was to determine the levels of VT and burnout experienced by a group of nurses, and to develop, implement and evaluate an intervention programme in order to promote the use of effective coping strategies to reduce the impact of VT and burnout. The researcher used the model of social constructivism to explore the social interactions between people as the basic factor that forms and influences behaviour, thought and emotion. Sixty nurses working at the Free State Psychiatric Complex participated in this study. They were randomly assigned and divided into control and experimental groups and then completed questionnaires to gather background information (biographical questionnaire) and to assess the characteristics of VT and burnout. The measurements used in this study include the Traumatic Stress Inventory (TSI) Belief Scale, the Traumatic Stress Inventory (TSI) Inner Experience Questionnaire, and the Maslach Burnout Inventory. A comparison of the mean scores on the characteristics indicated that experimental groups had significantly higher mean scores than the control group as far as connection and personal accomplishment are concerned. However, scores relating to affect tolerance, self-worth, trauma symptoms belief, emotional exhaustion, and depersonalisation did not differ significantly. This suggests that the programme implemented in this study was effective in improving a sense of connection and personal accomplishment in nurses. The aim of this programme was to assist nurses in understanding VT, to aid in transforming and addressing VT, to identify signs, symptoms and contributing factors of VT, and to develop a personal resource list in order to ensure the development of a healthy self.
Keywords: Dissertation (M.Soc.Sc. (Clinical Psychology))--University of the Free State, 2004; Psychiatric nurses; Nurse and patient; Psychiatric rating scales; Psychic trauma; Post-traumatic stress disorder; Traumatic stress inventory (TSI); Belief scale; Inner experience questionnaire; Maslach burnout inventory; Vicarious traumatisation; Secondary stress disorder; Coping strategies; Intervention programme; Burnout; Stress; Nurses